A Bibliometric Analysis of Government Budget Efficiency and Effectiveness: Trends and Future Directions - Loso Judijanto; Weda Febriyanto; Tera Lesmana (West Science Interdisciplinary Studies, 2024)
This study conducts a comprehensive bibliometric analysis of the literature on government budget efficiency and effectiveness, spanning publications from 1956 to 2024. Utilizing data exclusively from Google Scholar and employing VOSviewer for visualization, the analysis identifies key trends, influential themes, and research gaps within the field. The centrality of "effectiveness" in the literature underscores its critical role in public administration and fiscal policy, while emerging topics such as "policy," "cost effectiveness," and "e-government" highlight the growing importance of integrating economic efficiency and digital innovation into government budgeting practices. Persistent challenges, including issues of "transparency" and "corruption," indicate areas that require ongoing attention to enhance the overall effectiveness of government budgetary processes. The study's findings offer valuable insights for policymakers and researchers, suggesting a balanced approach that incorporates strategic policy-making, technological advancements, and robust accountability measures to optimize the use of public resources.